2021
DOI: 10.1101/2021.09.28.462252
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sustained Released of Bioactive Mesenchymal Stromal Cell-Derived Extracellular Vesicles from 3D-Printed Gelatin Methacrylate Hydrogels

Abstract: Extracellular vesicles (EVs) represent an emerging class of therapeutics with significant potential and broad applicability. However, a general limitation is their rapid clearance after administration. Thus, methods to enable sustained EV release are of great potential value. Here, we demonstrate that EVs from mesenchymal stem/stromal cells (MSCs) can be incorporated into 3D-printed gelatin methacrylate (GelMA) hydrogel bioink, and that the initial burst release of EVs can be reduced by increasing the concentr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…In contrast, gelatin is more biocompatible and has better thermal stability than collagen. In addition, several methods to enhance properties of gelatin, such as hybridization with other polymers, crosslinking strategies, and chemical modifications, are currently being assessed [ [96] , [97] , [98] ]; these are likely to broaden the scope of gelatin hydrogel applications. In 2000, Bulcke et al.…”
Section: Hydrogelsmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, gelatin is more biocompatible and has better thermal stability than collagen. In addition, several methods to enhance properties of gelatin, such as hybridization with other polymers, crosslinking strategies, and chemical modifications, are currently being assessed [ [96] , [97] , [98] ]; these are likely to broaden the scope of gelatin hydrogel applications. In 2000, Bulcke et al.…”
Section: Hydrogelsmentioning
confidence: 99%
“…In particular, Born et al. [ 97 ] evaluated the feasibility of GelMA hydrogels loaded with MSC-EVs for 3D bioprinting. The results showed that experiencing 3D bioprinting and light curing did not affect the activity of EVs, and indicated that 7% GelMA may be a more appropriate bioink concentration.…”
Section: Hydrogelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among various hydrogel bioprinting materials, GelMA biopolymer has become most widely used material owing to its unique features such as outstanding biocompatibility and tunable characteristics and mechanical properties to better mimic native ECM 20,21 . Currently, Born and coworkers developed GelMA bioink for the release of extracellular vesicles and reduced initial burst release by increasing the concentration of cross linker during gelation 22 . Nevertheless, hydrogel based bioinks generally cannot meet all needs for direct bioprinting with high fidelity of constructs because of their limited printability, 6,23 insufficient rheological properties, slow gelation, 24 and inadequate mechanical strength 25,26 .…”
Section: Introductionmentioning
confidence: 99%
“…20,21 Currently, Born and coworkers developed GelMA bioink for the release of extracellular vesicles and reduced initial burst release by increasing the concentration of cross linker during gelation. 22 Nevertheless, hydrogel based bioinks generally cannot meet all needs for direct bioprinting with high fidelity of constructs because of their limited printability, 6,23 insufficient rheological properties, slow gelation, 24 and inadequate mechanical strength. 25,26 In particular, it is demonstrated that GelMA bioinks could be printed at higher concentrations, but high concentrations exhibit a challenge for the survival of encapsulating cells.…”
Section: Introductionmentioning
confidence: 99%